Outdoor wildlife motion triggered camera - Shafika Binti Suhaimi (School of Microelectronics, University Malaysia Perlis, 2015)
This project Outdoor Wildlife Motion Triggered Camera is develop to help biologist monitor and study about the wildlife behavior and natural habitat so they can control the wildlife extinction. This project are using 8051 microcontroller and interfacing with 3 parts that is sensor, camera and SD card breakout board. The sensor detect the presence of wildlife and triggered the camera to capture the scene and automatically save the shot taken into external SD card. C programming language are written into 8051 microcontroller in order to operate the sensor, camera and external SD card.